A Juridical Review of the Role of Land Deed Officials (PPAT) in the Implementation of the Deed of Mortgage Rights - Tjandraningsih, Dewi (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
This research aims to analyze the juridical review of the role of Land Deed Officials (PPAT) in the implementation of the deed of mortgage rights. The study seeks to determine the position of Land Deed Officials (PPAT) in the execution of mortgage deeds and to identify the challenges encountered as well as the methods to overcome these obstacles in the process of mortgage rights imposition. The research adopts a socio-legal approach, utilizing data from both field research (interviews) and literature studies. Data analysis is conducted systematically, including data reduction, data presentation, and drawing conclusions. The findings conclude that the role of Land Deed Officials (PPAT) in the imposition of mortgage rights is to mediate between the interests of the debtor and the creditor, ensuring that both parties achieve a sense of justice, benefit, and legal certainty in securing mortgage rights. One of the challenges faced by PPAT in the implementation of mortgage rights is that some banks still allow the imposition of mortgage rights on unregistered land, a practice that carries significant risks.